Classificação e crescimento de grupos ecológicos da floresta ombrófila mista na flona de São Francisco de Paula, RS. - Gomes, Juliana Fernandes (2005)
The present work was realized in a Mixed Rainy Forest in Rio Grande do Sul, Brazil, that consists in one of the richest forest types that the State has. Due to the importance of conservation and the adequate use of natural forests, and the deficiency of specific studies of factors that influence the Mixed Rainy Forest growth in Rio Grande do Sul, it becomes necessary to know and relate this factors to evaluate the growth dynamics in mixed forests of araucaria, interacting with the site that they are. In this study were identified and characterized the different ecological groups at FLONA in São Francisco de Paula, Rio Grande do Sul, aiming to understand its composition and dynamics, important factors to develop sustainable management plans. The chosen area was the National Forest of São Francisco de Paula (between 29° 23` and 29 S; 50° 23` 50 W), 1.606, 69 ha, located in the county of São Francisco de Paula, in the region of Campos de Cima da Serra. Ten permanent plots of 1 ha from PELD were taken as reference, were systematically chosen, one 10 x 100 m strip from each plot, totalizing 1 ha. Inside this strips, the vegetation was inventoried, where all the floristic and biometric parameters of all individuals with CAP ≥ 30 cm were evaluated, later dendrometric tapes were installed to verify the annual and seasonal growth. The density by specie formed a matrix (99x39) used in the multivariate analysis. The vegetation grouping presence from FLONA was tested through TWINSPAN (Two-way indicator species analysis), since this three ecological groups were veryfied. The Group 1 was named because shows characteristics from the climax stage of the Mixed Rainy Forest , so it was denominated Primary Forest; The Group 2 (humid site forests) showed an adapted behavior to places with humidity influence; and the Group 3 (Secondary Forest) was characterized to show species with pioneer behavior. The indicator species of the groups were: Araucaria angustifolia (Bertol.) Kuntze (Group 1); Sebastiania commersoniana (Bail.) L. B. Sm. et Dows, Ocotea pulchella Mart., Eugenia uruguayensis Cambess. and Eugenia psidiiflora O Berg (Group 2); and Sebastiania brasiliensis Spreng (Group 3). After the ecological groups formation, these were characterized due to the floristic composition, dendrometric parameters and growth. To evaluate the relation of environmental factors responsible by the groups formation it was used the same density matrix, where, based on the Canonical Correspondence Analysis (CCA) showed that group 1 occurs is less sloping places, rocky, with deep soils and well drainage; group 2 occurs in less sloping places, with very humid soils, sometimes shallow and rocky; group 3 occurs in exposed and sloping places, with soils sometimes shallow and rocky. The Canonical Correspondence Analisys showed what the ecological factors are essential to ecological groups formation. The circumference growth was higher in summer, followed by spring, autumn and winter.